PENINGKATAN KREATIVITAS ANAK UMUR 7-8 TAHUN MELALUI PENDAMPINGAN SESI AKTIVITAS IBADAH ANAK DARING - Ratnasari, Anisza (Servirisma, 2023)
The pandemic has forced children to play, study and worship at home. However, online children's worship must have the same purpose as the previous ones. Praise, stories and activities are created by considering the child's physical, cognitive, motor and verbal abilities. This activity, which is part of the GKI GS children's commission, is carried out online every Sunday at 10.30-11.45 WIB. The implementation focuses on children aged 7-8 years (grade 2), totaling 47 children. Mentoring includes activity sessions. Lecturers interactively and innovatively package and deliver each session through various creative learning media. Feedback, which is a photo or video of activity sent through the parent group. The curriculum adapts to the elementary school academic calendar. In the first 2 (two) months, less than 20% of children gave feedback, but in March-May the number of feedbacks increased. Although children's worship is currently online, through mentoring activity sessions that are packaged creatively to support the theme of worship, it is hoped that children will be more active, interactive, increase learning motivation and of course increase children's creativity.